Product Quality and Price its Influence on the Decision to Purchase a Realme Handphone on Libra Cell - Asyraf, Fadhil; Montazeri, Muhammad Haidar; Romdonny, Jefry (PT FORMOSA CENDEKIA GLOBAL, 2024)
Technology is currently developing increasingly rapidly. This applies to familiar communication tools, namely smartphones. With advances in technology, people are interested in enjoying technology so people often buy smartphones based on desire, not because of need. Therefore, this research aims to determine the influence of product quality and price on Realme smartphone purchasing decisions, empirical study; Libra Cell. The number of respondents was 100 people, with sample criteria; realme smartphone users and Libra Cell consumers. The sample used uses a non-probability sampling technique. The method used is purposive sampling, namely a sampling technique with certain considerations, so the samples selected are people who meet the criteria mentioned above. By using Structural Equation Modeling (SEM), the methods used include; validity and reliability analysis (smartPLS 4.0). The result is that product quality has a positive and significant effect on purchasing decisions and the price variable has a positive and significant effect on purchasing decisions. Realme needs to improve and develop product quality and smartphone prices so that the company can know what factors can motivate people to buy Realme smartphones. However, it should be noted that purchasing decisions are influenced by several other factors that are beyond the scope of this research.